Cities economies in a warming world: An in-depth study of long-run and short-run climate change impact in China - Yu Song; Na Huang; Kang Jiang; Xiao Chen; Riping Gao; Jingyu Men; Pengshuai Bi; Zhihua Pan (Sustainable Futures)
Understanding the economic impacts of climate change is crucial for shaping effective policy responses. This study examines the relationship between historical temperature fluctuations and economic growth in Chinese cities from 1999 to 2018. Using a stylized growth model and panel data analysis, we assess both short-term and long-term effects of temperature variations on overall economic output and sector-specific performance across agriculture, manufacturing, and services. Our findings reveal a non-linear temperature-economic growth relationship, with significant short-run disruptions and long-lasting sectoral impacts. While the agricultural sector benefits from moderate warming, manufacturing and services experience adverse effects over time. Moreover, low-income cities and those with specific industry structures exhibit heightened vulnerability to climate fluctuations. Projections suggest potential annual economic impacts ranging from −0.4 % to 0.2 % on per capita income growth, with cumulative effects leading to a −1 % to 15 % change in per capita GDP by the end of the century. These results underscore the necessity for targeted adaptive strategies and low-emission economic pathways to mitigate climate-induced economic risks.